2007
DOI: 10.2172/919082
|View full text |Cite
|
Sign up to set email alerts
|

A study of neutrino oscillations in MINOS

Abstract: MINOS is a long-baseline neutrino oscillations experiment located at Fermi National Accelerator Laboratory (FNAL), USA. It makes use of the NuMI neutrino beamline and two functionally identical detectors located at distances of ∼1 km and ∼735 km from the neutrino production target respectively. The Near Detector measures the composition and energy spectrum of the neutrino beam with high precision while the Far Detector looks for evidence of neutrino oscillations.This thesis presents work conducted in two disti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 80 publications
0
19
0
Order By: Relevance
“…In a previous analysis [142], it was found that the Near Detector neutral current selected spectrum is affected by an overestimate of events due to the presence of badly reconstructed events which are characterised by a low energy shower. In most of the cases poorly reconstructed events are activity generated in a charged current interaction which the reconstruction algorithm fails to recognise as connected to the main activity area and reconstructs as a small independent event.…”
Section: Near Detector Preselectionmentioning
confidence: 96%
See 3 more Smart Citations
“…In a previous analysis [142], it was found that the Near Detector neutral current selected spectrum is affected by an overestimate of events due to the presence of badly reconstructed events which are characterised by a low energy shower. In most of the cases poorly reconstructed events are activity generated in a charged current interaction which the reconstruction algorithm fails to recognise as connected to the main activity area and reconstructs as a small independent event.…”
Section: Near Detector Preselectionmentioning
confidence: 96%
“…Given the MINOS detector characteristics, there is not much shape information on the hadronic shower development that can be exploited to select neutral current events. Alternative methods to the one presented in this thesis have been studied [142,141,143,144]: the most powerful variables to select neutral current events are the ones which try to identify and reject the muon tracks. The inelasticity y is defined as the fraction of the neutrino energy E ν that is converted into hadronic energy E hadr :…”
Section: Neutrino Eventsmentioning
confidence: 99%
See 2 more Smart Citations
“…A set of cleaning requirements [98] have been developed. The cleaning requirements are a combination of timing and topological cuts.…”
Section: Data Cleaningmentioning
confidence: 99%